A highly selective and sensitive fluorescent nanosensor for dopamine based on formate bridged Tb(iii) complex and silver nanoparticles. Issue 22 (17th August 2017) - Li, Huihui; Shen, Jin; Cui, Rongwei; Sun, Chongmei; Zhao, Yanyan; Wu, Xia; Li, Na; Tang, Bo
Abstract : The proposed fluorescent nanosensor can distinguish DA from EP. Abstract : Highly selective determination of dopamine (DA) over other catecholamines is an urgent need for the precise diagnosis and therapy of DA related diseases. Herein, a new formate-bridged Tb(iii )-complex and silver nanoparticles (AgNPs) enhanced fluorescent nanosensor was constructed. HCOO − acted as a co-ligand of Tb(iii ) and also as a linker between the Tb(iii ) complex and AgNPs and more readily combined with the primary amine of DA than with epinephrine (EP). The formate-bridged action strengthened AgNPs-based surface enhanced fluorescence of the Tb 3+ -DA complex and improved the selectivity towards DA. Under neutral buffer conditions, the detection limit for the assay of DA was down to 0.15 nM ( S / N = 3) with a linear range from 0.5 nM to 100 nM ( R 2 = 0.9978). Furthermore, the nanosensor could successfully distinguish DA from EP.